Syndrome of Thyrotoxicosis, Approaches to Diagnosis and Treatment (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Thyrotoxicosis has multiple causes, in most cases it develops due to excessive synthesis of thyroid hormone (hyperthyroidism). The most common reasons of thyrotoxicosis are Graves' disease, multinodular toxic goiter and toxic adenoma. Clinical manifestations of thyrotoxicosis are independent of its causes, but have their own features in different diseases. The therapy depends on the etiology of the disease, thyroid size, presence of complications and comorbidities. Antithyroid drug, radioactive iodine therapy or surgery are shown in an excessive biosynthesis of thyroid hormones. Destroid forms of thyrotoxicosis with the release of stored hormones does not required antithyroid therapy. For any symptomatic thyrotoxicosis need βblockers. Key words: thyrotoxicosis, hyperthyroidism, Graves' disease, thionamides. Thyrotoxicosis is a syndrome in which there are clinical and biochemical manifestations of excessive levels of thyroid hormones in the blood, regardless of the reason for the increase in their level. Hyperthyroidism is a condition caused by excessive synthesis and secretion of thyroid hormones by the thyroid gland (TG) [1]. Thus, the terms thyrotoxicosis and hyperthyroidism are not synonymous, although in foreign literature they are often used as identical. The frequency of thyrotoxicosis is approximately 2% among women and 0.2% among men [2 In most cases, thyrotoxicosis is associated with Graves' disease (GD), multinodular toxic goiter and toxic adenoma [4].